Mass transport of solutes in saturated porous media flow : an analytical and numerical study - Salhotra, Atul Mohan; Banks, Robert B.; Gupta, Ashim Das; Nguyen, Cong Thanh, IeExamination Committee; His Majesty The King of Thailand (Bangkok : Asian Institute of Technology, 1981)
The mass balance equation for the transport of a solute in porous media considering the effects of convection, molecular diffusion, mechanical dispersion, degradation and interphase mass transfer is derived. The equation is presented for the generalized flow case. Analytical solutions to a few simple cases of the mass balance equation in a homogenous, isotropic, saturated and infinite porous media with steady unidirectional flows are presented. The source inputs consist of either time-variable or constant input concentrations of contaminants. The solutions predict the concentrations of contaminants as a function of time and space for prescribed medium and fluid properties. Two numerical models to solve the convection-diffusion equation are developed. The model results agree well with available analytical solutions. A complete solution to a three-dimensional source-sink flow problem is presented.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Water, Underground -- Pollution; Porous materials